New vounds from a search for muonium to antimuonium conversion - Willmann, Lorenz; Schmidt, Peter Vaughan; Grossmann, Alex; Jungmann, Klaus; Meyer, Volker; Merkel, Jesko Friedrich; Putlitz, Gisbert zu; Reinhard, Irene; Träger, Konrad (Physical review letters, 1999)
A new upper limit for the probability of spontaneous muonium to antimuonium conversion was established at PM¯M≤8.3×10−11 ( 90% C.L.) in 0.1 T magnetic field, which implies consequences for speculative extensions to the standard model. Coupling parameters in R-parity-violating supersymmetry and the mass of a flavor diagonal bileptonic gauge boson can be significantly restricted. A Z8 model with radiative mass generation through heavy lepton seed and the minimal version of 331 models are disfavored.